Permainan Balistik untuk Meningkatkan Hasil Belajar Gerak Dasar Manipulatif Siswa Sekolah Dasar - Nuryanto, Hari (Jurnal Didaktika Pendidikan Dasar, 2018)
Learning acitivities through ballistic game was meant to improve the third grade children’s manipulative basic movements in the Public Elementary School 2 Tlogolele. This innovative learning with basic movements was implemented for physical education in the Public Elementary School 2 Tlogolele. There were nineteen pupils recruited for this study in the Academic Year 2016/2017. Data collection used an observation checklist. The obtained data were analyzed descriptively and quantitatively. Research results show there is an improvement in the pupils’ learning outcomes with the mean score = 21% prior observation and 84% after innovative learning.  In conclusion, learning with ballistic game could improve children’s manipulative basic movements in the Elementary School 2 Tlogolele in the academic year of 2016/2017.